2000
DOI: 10.1111/j.1572-0241.2000.03367.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Homocysteine in Patients With Crohn's Disease Are Related To Folate Levels

Abstract: Homocysteine levels are increased in patients with Crohn's disease and this finding is inversely correlated with folate levels. Supplementation of folate to patients with Crohn's disease may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 23 publications
2
31
3
Order By: Relevance
“…We did not find significant correlation between age, disease activity, medication, smoking status, and Hcys levels in this UC cohort. Chowers et al [33] , have observed similar findings in a group of patients with CD.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…We did not find significant correlation between age, disease activity, medication, smoking status, and Hcys levels in this UC cohort. Chowers et al [33] , have observed similar findings in a group of patients with CD.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 68%
“…Increased Hcys levels and high prevalence of hHcys in IBD patients have been reported in previous studies [31][32][33][34][35][36] . In our study, similar findings were observed in this cohort of UC patients with a slightly higher prevalence of hHcys (30%) than in other studies (10-26%) [31,32,35,36] .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, a number of disorders suggested to benefit from treatment with fish oil are associated with low folate or with a marker of low folate status, homocysteine (Jacob et al, 1994). These disorders include Crohn's disease (Belluzzi et al, 1996;Chowers et al, 2000), rheumatoid arthritis (Kremer et al, 1987;Schroecksnadel et al, 2003), mania (Hasanah et al, 1997;Stoll et al, 1999a, b) and hostility (Stoney and Engebretson, 2000;Iribarren et al, 2004). One study suggests that folate, like fish oil, can lower triglycerides, LDL and cholesterol (Connor et al, 1993;McGregor et al, 2000).…”
Section: Discussionmentioning
confidence: 99%